2018
DOI: 10.1097/sap.0000000000001583
|View full text |Cite
|
Sign up to set email alerts
|

Review of the First 108 Free Flaps at Public Health Concern Trust–NEPAL Hospitals

Abstract: Reconstructive microsurgery is challenging in Nepal and more generally in developing settings. However, persistent technical support such as training and workshops can make it feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…There was no evidence of graft failure in any of the patients followed up in this study. This compares favourably with most studies reporting the survival rate of vascularised tissue used in microsurgical mandibular reconstruction in LMICs, which is 50%–100% survival 28–32,34,35 . It should be noted that the study reported 100% survival was a series of 22 patients in India treated by an experienced team over a period of 6 months, with flap observations performed frequently overnight by an anaesthetist.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…There was no evidence of graft failure in any of the patients followed up in this study. This compares favourably with most studies reporting the survival rate of vascularised tissue used in microsurgical mandibular reconstruction in LMICs, which is 50%–100% survival 28–32,34,35 . It should be noted that the study reported 100% survival was a series of 22 patients in India treated by an experienced team over a period of 6 months, with flap observations performed frequently overnight by an anaesthetist.…”
Section: Discussionsupporting
confidence: 62%
“…This compares favourably with most studies reporting the survival rate of vascularised tissue used in microsurgical mandibular reconstruction in LMICs, which is 50%-100% survival. [28][29][30][31][32]34,35 It should be noted that the study reported 100% survival was a series of 22 patients in India treated by an experienced team over a period of 6 months, with flap observations performed frequently overnight by an anaesthetist. In addition, they do not disclose the duration that patients were followed postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a select few centres in LMICs are undertaking these procedures as part of standard practice (15)(16)(17). Local and regional alternatives do exist, however many of these are also technically demanding, and even with extensive training, microsurgical equipment and techniques, they are vulnerable to complications requiring further surgery (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Performing microsurgery in LMICs is challenging, even for experienced teams. However, a select few centres in LMICs are undertaking these procedures as part of standard practice [16][17][18]. Local and regional reconstructive alternatives do exist (e.g.…”
Section: Introductionmentioning
confidence: 99%